Neonatal mortality and its determinates in public hospitals of Gamo and Gofa zones, southern Ethiopia: prospective follow up study - Abera Mersha; Agegnehu Bante; Shitaye Shibiru (BMC, 2019)
Abstract Background The neonatal period is the most vulnerable time for child survival. The declines in the neonatal mortality rate have been slower than the post-neonatal under-five mortality rate in the majority of countries. This trend is also similar in Ethiopia, that neonatal mortality was high as compared to the post-neonatal mortality rate. A large proportion of neonatal deaths occur during the 48 h after delivery. Different studies were conducted in assessing determinates for neonatal mortality but there is a need to assess the immediate postnatal (within 2 days following delivery) cause of neonatal mortality that the majority of deaths occurred at that time. So, this study is to fill those gaps of the aforementioned studies, in assessing the determinate factors affecting neonatal mortality in public hospitals of Gamo and Gofa Zones, Southern Ethiopia. Methods A prospective follow up study was conducted among 6769 study participants from April 5, 2018, to March 5, 2019. All live births at the hospitals during the study period were included in this study. A structured verbal autopsy questionnaire was used to collect the data on the causes of neonatal death. Data were entered into Epi data version 3.1 and exported to Stata version 15 for analysis. Crude and adjusted estimate β with 95%CI was calculated in the binary logistic regression model. A log-likelihood ratio (LR) was tested for goodness of fit. In this study P-value < 0.05 was considered to declare a result as a statistically significant association. Results In this study, neonatal mortality incidence ratio was 9.6 (95%CI: 7.5, 12.2) per 1000 live births. Age of the mother, number of antenatal care visits, sex of the neonate, presentation, and gestational age were identified as the significant determinates for neonatal mortality cases. Prematurity, infection, and birth asphyxia were the most common causes of neonatal mortality cases. Conclusions This study indicated that a significant number of neonates died during the neonatal period. Both maternal and neonatal factors were identified. Therefore, early identification of obstetric complications and immediate interventions, strengthening the provision of quality antenatal and postnatal care services are recommended.